2020
DOI: 10.1007/s00167-020-05902-z
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps tendon anterior cruciate ligament reconstruction

Abstract: Quadriceps tendon is a promising alternative graft option for anterior cruciate ligament (ACL) reconstruction, which can be harvested with or without a bone block as well as a full or partial thickness graft. Therefore, quadriceps tendon graft could be used in primary and revision ACL reconstruction based on the requirements (tunnel size, tunnel position, etc.). The all soft tissue, partial thickness quadriceps tendon graft in detail and pitfalls of the harvest are described in the present review. After quadri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 75 publications
0
72
0
Order By: Relevance
“…30 An advantage of the QT graft for anatomic ACL reconstruction is the opportunity to harvest a full-thickness graft as well as a partial-thickness tendon graft with or without an additional bone block. 5 So far, several clinical studies have demonstrated good to excellent clinical outcome scores after anatomic ACL reconstruction using QT graft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 An advantage of the QT graft for anatomic ACL reconstruction is the opportunity to harvest a full-thickness graft as well as a partial-thickness tendon graft with or without an additional bone block. 5 So far, several clinical studies have demonstrated good to excellent clinical outcome scores after anatomic ACL reconstruction using QT graft.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interest has arisen in the quadriceps tendon (QT) as an alternative autologous graft option for primary ACL reconstruction. 5,31 This graft shows morphologic and biomechanical characteristics that produce a suitable graft for ACL reconstruction. 30,33,35 In a cadaveric study, ACL reconstruction using a QT autograft resulted in similar knee stability compared with using a quadrupled semitendinosus-gracilis tendon autograft.…”
mentioning
confidence: 99%
“…As a common athletic injury, ACL rupture can cause serious damage such as knee joint instability, injury to other ligaments, dislocation, and osteoarthritis [2,3]. ACL reconstruction is currently consid-ered the gold standard for treating ACL rupture, and grafts including autografts, allografts, and synthetic grafts are used for this purpose [4][5][6]. However, these grafts have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 12 The use of allograft in comparison to autograft has also been identified as a risk factor for reconstruction failure, especially in younger more active patients. 7 It is important to note that regardless of graft type, anatomic ACLR is considered the benchmark, reconstructive technique, 13 as it has been shown that anatomic ACLRs reduce the risk of posttraumatic osteoarthritis (OA) at long-term follow-up. 14 Given the multitude of graft options and risk factors for failure, it is critical that the operating surgeon have a comprehensive discussion with the patient regarding which graft option(s) would be most suitable for the patient's individualized reconstruction, particularly given that the surgeon's recommendation has been shown to be one of the most important factors behind the patient's graft choice.…”
Section: Graft Choicesmentioning
confidence: 99%